A high-molecular weight exopolysaccharide from the Cs-HK1 fungus: Ultrasonic degradation, characterization and in vitro fecal fermentation. (15th October 2020) - Mao, Yu-Heng; Song, Ang-Xin; Li, Long-Qing; Yang, Yan; Yao, Zhong-Ping; Wu, Jian-Yong
Graphical abstract: Highlights: Exopolysaccharide (EPS) of Cs-HK1 fungus was treated by power ultrasound (US). Exopolysaccharide US treatment of EPS reduced the aggregate size and average molecular weight (MW). The lower MW EPS fractions were fermented more rapidly in fecal culture. Reduction of EPS MW affected the relative abundance of microbial populations in fecal microflora. Abstract: This work was to examine the impact of power ultrasound (US) on the molecular properties of a high-molecular weight (MW) exopolysaccharide (EPS) from the Cs-HK1 medicinal fungus and the utilization, and prebiotic function of the US-treated EPS fractions in human fecal microflora in vitro . The US treatment caused notable reduction of intrinsic viscosity, average MW and aggregate size of EPS in water but no significant changes in the molecular structure. The US-treated EPS fractions were consumed more rapidly by the fecal microflora, resulting in a higher total level of short chain fatty acids. They also affected the relative abundance in the microflora more beneficially than the original EPS. The results suggest that power US is effective for modifying and improving the prebiotic properties of high-MW polysaccharides.